Effect of Tidal Fluctuation on the Stability of Estuarine Structures in Sarawak - Kaniraj, S.R; Lee, L.J.; Taib, S.N.L. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Several incidents of lateral movement and failures of estuarine structures have been reported in Sarawak. These structures located in very soft and deep sedimentary soils are usually supported on pile foundations. There is a 4 to 7 m daily tidal fluctuation in these locations, the effect of which on the ground and the piles is usually neglected in design. A study has been undertaken to formulate improved approaches for the design of riverine and estuarine structures. The validation of a theoretical model requires data on ground movement and pore water pressure changes due to tidal fluctuation. Accordingly, piezometers and inclinometer casings were installed at the sites of two structures where a bridge and jetty are proposed to be constructed. The inclinometers measure the lateral movement of the river banks and a pile installed in the riverbed. The piezometer and inclinometer readings are being recorded periodically. The paper explains the background of the study, case histories of failures, soil conditions at the two sites, details of instrumentation, results of measurement, and the interpretations.